Ukrainian Religious Studies in the Context of World Religion Science - Fylypovyč, Ljudmyla Oleksandrivna (Ukrai͏̈ns'ke relihijeznavstvo, 2006)
Ukrainian religious studies has recently entered the world scientific community. Acquaintance with Western science, which has proven to be heterogeneous, often based on different methodological approaches and methodological means, has coincided with difficult internal transformations that have undergone all humanitarian knowledge in Ukraine after worldviews and political changes in society. In pursuit of its identity, domestic religious studies went, on the one hand, by contrasting itself with theology, and on the other, by distinguishing itself from scientific atheism. At first, the emergence of religious studies from the bosom of ideologized social science was more relevant. In the form of a critical study of religion, Soviet-era religious studies were included in scientific atheism. Therefore, religious studies came not as knowledge of religion, but as its critique.